Análise do estágio supervisionado de cursos de Administração à luz da aprendizagem em ação. - Rego, Sidnéia Maia de Oliveira (2013)
This study aims to analyze the process of supervised stages of the course from administration the perspective of action learning, to serve this purpose were established as specific objectives: describe the process in Supervised stages Administration course in two Higher Education Institutions; identify the perceptions of the students during the learning experience Stages Supervised and set facilitating factors and limiting the Supervised learning. The research was conducted in two higher education institutions in the Northeast, one public and one private. Theories of adult learning and experiential learning formed the basis for investigations which were buoyed by the Learning in Action The research part of a qualitative conception, as a form of interpretive research, we opted for the multiple-case study, the subjects of research were selected according to availability to participate in the study, 20 people participated in the survey. Data were collected through semi-structured interviews with two course coordinators, four sessions were held focus groups with 9 students and 9 teachers in both Higher Education Institutions. The results revealed that the process of supervised training is institutionalized in Educational Projects Course, according to the legislation. The institutions have different ways of offering the internship, in common, is the association between stage and Work of Course Completion. In private institution stage occurs through two modes, the traditional format, the student performs supervised internship in an organization and presents the final monograph, another modality through simulated business, students makes interactions similar to the real world and report the experience. In public institution, the student enrolled in the disciplines of Stages supervised, is not linked to an organization, their contact is limited to data collection, the development stage is linked to the End of Course Work in monograph form or intervention project However, students and teachers, say the monograph prevails. The learning in supervised training was not perceived as a priority, the prevailing concern in performing the Work of Course Completion. Among the factors that facilitate the learning stage, is the motivation of the students who appear eager to experience practical experiences among the limiting factors, structure problems, few teachers in relation to student numbers and cultural problems, were more pointed in speeches. The voluntary internship emerged as an alternative for courses taking better learning experiences in these activities, look more priority, considering that all formal structure is already mobilized by the Institution of Higher Education, which designates a supervisor and internship requires the preparation of Final report to the Learning in Action can provide a favorable way for operationalization of this activity.